Exploration of Career Development Through TikTok in Improving Student Career Planning - Firmansyah, Muhammad Yunus; Isriyah, Mudafiatun; Rahmawati, Weni Kurnia (IAIN Kudus, 2024)
Exploration of Career Development Through TikTok in Improving Student Career Planning. This research aims to determine the contribution of the TikTok in improving student career planning and creating digital culture as a forum for Career Development Exploration (EK), to find out the results of material expert validation tests and the results of media expert tests on career development exploration through TikTok in improving planning final semester student career at PGRI Arghopuro University Jember. This research uses a type of research and development or what is known as R&D (Research and Development) using the ADDIE model up to stage 5. Technique Data collection is in the form of an assessment sheet. Data analysis using qualitative and quantitative analysis. Based on the results The BK material expert's assessment of the exploration of career development through TikTok in improving career planning received a score of 85 with the